The idea of mindfulness into educational practice - Kowalska, Róża (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Many changes taking place in the postmodern world – the increasing pace of life, new channels of communication, consumerism – make the man less and less attention is paid to care about the quality of daily life, relationships and self-reflexivity. Practicing mindfulness ideas, understood as a special kind of attention – conscious, targeted at the moment and nonjudgmental, affecting among other things, strengthening competencies important for building relationships. These aspects can significantly influence not only on strengthening contacts with other people – also becomes relevant dimension reflexivity, self-acceptance and to maintain better contact with the fullness of existence. A person who practices mindfulness can increase concentration, better cope with stress, stimulate their creativity and develop emotional intelligence.
Keywords: Buddhism; education; mindfulness; mindfulness practice